Rancangan Atribut Data Pada Informasi Spasial Satuan Kerja Perangkat Daerah (Pendidikan) Untuk SIGDa Kabupaten Lombok Barat - Agus Pribadi (Universitas Bumigora, 2016)
Education management is an important part of human resources management in the governmental region. Local government is using spatial information in the SIGDa to support composing of development program planning. A part of SIGDa is spatial information of education feld in which authorizes by agency of education youth and sport of government of West Lombok Regency. Spatial information of education feld is able to support governmental decision making and development program planning for education feld. Basically, web-SIGDa Lombok Barat can be equipped with spatial data information based on governmental agency. Spatial information for development program planning of government needs comprehensive attributes. The comprehensive attributes are needed to build good spatial information what used for composing of development program planning. Requirement of spatial information attributes can be used for reference in the sub system development of SIGDa Lombok Barat. The sub system of SIGDa Lombok Barat development constitutes spatial information for governmental agencies on the government of West Lombok Regency.